Complete genome sequence of Ilumatobacter coccineum YM16-304T. Issue 3 (May 2013) - Fujinami, Shun; Takarada, Hiromi; Kasai, Hiroaki; Sekine, Mitsuo; Omata, Seiha; Harada, Takeshi; Fukai, Rieko; Hosoyama, Akira; Horikawa, Hiroshi; Kato, Yumiko; Nakazawa, Hidekazu; Fujita, Nobuyuki
Abstract Ilumatobacter coccineum YM16-304T (=NBRC 103263T ) is a novel marine actinobacterium isolated from a sand sample collected at a beach in Shimane Prefecture, Japan. Strain YM16-304T is the type strain of the species. Phylogenetically, strain YM16-304T is close toIlumatobacter nonamiense YM16-303T (=NBRC 109120T ), Ilumatobacter fluminis YM22-133T and some uncultured bacteria including putative marine sponge symbionts. Whole genome sequence of these species has not been reported. Here we report the complete genome sequence of strain YM16-304T . The 4, 830, 181 bp chromosome was predicted to encode a total of 4, 291 protein-coding genes.